Parents' and Teachers' Attitudes to Play and Drama in Education in Early Years Classrooms in Jiangsu Province, China - Carmel O’ Sullivan (Comparative Education Society of Iran ( CESIR), 2018)
Set against the background of the Chinese government's commitment to universalise early childhood educational provision, this exploratory study investigated the value attributed to play and drama-based teaching and learning in ECE from the perspectives of parents, teachers and Head Teachers from Suzhou in Jiangsu Province. We applied content and statistical analyses on the search results, and the findings indicate that while parents expressed interest in less regimented and more active, play-based approaches to education in their children's classrooms, broader societal and philosophical influences about the purposes of education prevail, and they are concerned about their children falling behind in a highly competitive education system. Teachers and Head Teachers are similarly aware of the value of play in young children's development, but lack the knowledge, skills and resources to implement a play-based approach to teaching and learning in their classrooms. The implications of the modernisation project in early childhood education in China is discussed.